Diagnostic imaging. - Moore, Kevin R.; Ross, Jeffrey S. (Philadelphia, PA : Elsevier, 2021)
Welcome to the third edition of Diagnostic Imaging: Spine. Five years have passed since the second edition, and 11 years have flown by since the first edition was published. This edition is a refresh with new images, new diagnoses, and updated text and references. The same excellent Amirsys formatting is present, with individual diagnoses capable of standing alone but with a logical integration within the larger sections. The Key Facts box retains its visual prominence at the beginning of each diagnosis, allowing for a quick scan of the most important bullet points when time is short (and when is it not?). The text format remains in the hallmark Diagnostic Imaging bulleted form that allows a large amount of important information to be displayed in an easy-to-use and inviting layout. Prose text chapters are included for the introduction to major sections, which are color coded, and the use of tables allows quick scanning for important data and measurements.--From the publisher.
Includes bibliographical references and index.
Keywords: Magnetic Resonance Imaging; Spinal Diseases; Spine